IMPLEMENTASI PEMBELAJARAN BERBASIS PROYEK (PJBL) UNTUK MENINGKATKAN KOMPETENSI MEMBUAT COFFE LATTE ART PADA KELAS XI KULINER A SMK NEGERI 3 TABANAN SEMESTER GANJIL TAHUN PELAJARAN 2022 /2023 - I Putu Gede Anom Darmawisata (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
This study aims to describe the use of the Project-Based Learning method for Culinary learning achievements of Class XI Culinary A students at SMK Negeri 3 Tabanan, Tabanan Regency in the 2022/2023 Academic Year. This classroom action research was designed in two cycles, in each cycle carried out for one month. At the end of the action of each cycle, monitoring and evaluation are carried out, which are then reflected in the results of the evaluation for planning the next cycle. Monitoring was carried out using observation techniques, interviews and student skills tests on the competence of making latteart coffee in the Barista Elective Subject. After using the learning process with the project-based learning method, students who do not understand how to make coffee latteartr. indicates a deeper understanding of making latteart coffee. in Barista Elective Subjects. Based on the results of the evaluation, it can be seen that in cycle I there was an increase in students' mastery of making latte art coffee in the subject of choice of the barista with the learning achievement score increasing from the average initial learning achievement score of 59.40 increasing to 68.72 with the percentage of mastery interpreting the model semiconductor atoms. in barista elective subjects by 15.69%. The average percentage increase in the level of Culinary learning achievement between before and after the first cycle of action was 29.61%. In cycle II, in the form of project-based learning techniques, there was an increase in the average value of student achievement from 68.72 to 78.48 with an increase in the percentage of mastery of interpreting the atomic model of semiconductor materials by 13.92%.